The Influence Of Promotion And Store Atmosphere At Cafe Kopitagram Cinere Depok On Consumer Satisfaction - Pradini, Gagih; Kusumaningrum, Anisa Putri; Syawal, Muhammad Rizky Alifa; Ermawati, Kris Cahyani; Anggraini, Fera Dhian (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2023)
This study aims to determine the analysis of promotions and store atmosphere on consumer satisfaction. Sampling for this study through primary data, namely by distributing questionnaires to as many as 100 respondents. The analysis techniques used are tests contained in SPSS 29 software. The results of this study show that promotional variables do not have a partial effect on consumer satisfaction, store atmosphere variables have a positive and significant effect on consumer satisfaction, and promotional variables and store atmosphere together have a positive and significant effect on consumer satisfaction. The conclusion of this study the store atmosphere variable is the most influential factor in consumer satisfaction